Clinical Predictors of Abnormal Head Computed Tomography Findings in Non-trauma Patients Presenting to a South African Emergency Department - Simwatachela, Ekin; Ozoh, John O.; Mabuza, Langalibalele H.; Kalinda, Chester (Frontiers in Radiology, 2021)
Background: Head Computed Tomography (head CT) examinations conducted at Emergency departments (EDs) for non-trauma patients are expensive and expose patients to ionizing radiation. Identification of symptoms likely to yield abnormal head CT scans can reduce costs and prevent unnecessary patient irradiation. There is limited comprehensive data in the literature concerning the utilization of head CT in low and middle-income countries (LMICs) EDs. Methods: A retrospective study of successive non-contrasted head CT scans from February 2017 through January 2018 performed on non-trauma ED patients aged 18 years and above without known pre-existing intracranial pathology was conducted. Univariate and multivariate logistic models were used to determine which presenting clinical features were likely to yield abnormal head CT findings. Clinical information was obtained from the history and physical examination findings entered on the requisition form by the ED clinicians and from previous head CT reports if present on the picture archiving and communication system (PACS). Results: 396 consecutive patients who received head CT examinations had a median age of 49 years (IQR: 36-53) and 53.3% were male (n=211/396). Of the head CT scans included, 73.5% of head CTs included were abnormal (n=291/396). Age greater than 61 years (aOR:1.54; 95%CI: 1.12-2.10), focal neurologic deficit (aOR: 2.46; 95%CI: 1.42-4.26), and loss of consciousness (aOR 2.82; 95%CI: 1.21-6.57) were the predictors of abnormal head CT findings. Conclusion: A head CT scan in a non-trauma patient presenting to an emergency department in a Low-Middle income country like South Africa is likely to yield abnormal findings if a patient presented with age above 61 years, loss of consciousness, or focal neurological deficit.